2009
DOI: 10.1021/ja902797j
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Dynamics of the P1 Helix within the Tetrahymena Group I Intron

Abstract: RNA conformational transformations are integral to RNA's biological functions. Further, structured RNA molecules exist as a series of dynamic intermediates in the course of folding or complexation with proteins. Thus, an understanding of RNA folding and function will require deep and incisive understanding of its dynamic behavior. However, existing tools to investigate RNA dynamics are limited. Here we introduce a powerful fluorescence polarization anisotropy approach that utilizes a rare base analog that reta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…[15] The EPR data obtained for Ç are in agreement with the fluorescence results. Analyses presented here further suggest that J1/2 modulates motional ordering of P1 in the 0.5–50 ns range.…”
supporting
confidence: 82%
“…[15] The EPR data obtained for Ç are in agreement with the fluorescence results. Analyses presented here further suggest that J1/2 modulates motional ordering of P1 in the 0.5–50 ns range.…”
supporting
confidence: 82%
“…We monitored the reactions under conditions in which the oligonucleotide substrate (S) is already bound to the ribozyme in the so-called open complex [(E•S) o , Figure 1a], because the open complex gives a defined state that involves only base pairing of S with the ribozyme that is not expected to be affected by modifications in the guanosine binding site. 10,40,41 To favor the open complex, we used the oligonucleotide substrate -1r,dSA 5 (see General kinetic methods ), in which specific 2′-OH groups that stabilize the docked state are replaced by 2′-H groups.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that intrinsic dynamics of P1 in the open complex, which control the ability of P1 to sample different conformations (e.g., open & closed complex), may be one of the factors responsible for the observed slow docking rate. 50, 52, 53 However, virtually nothing is known about intrinsic dynamics of any individual states in large folded RNAs such as the Tetrahymena ribozyme. The SDSL studies described above was the first example in which intrinsic dynamics of P1 in the nanosecond regime were probed experimentally in the context of the entire ribozyme, and the data revealed that intrinsic dynamics are modulated by structure (i.e., J1/2) and may influence function (i.e., substrate binding affinity and cleavage fidelity).…”
Section: Rna Dynamic Information Obtained Using Sdslmentioning
confidence: 99%